2018
DOI: 10.5194/acp-18-17655-2018
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected vertical structure of the Saharan Air Layer and giant dust particles during AER-D

Abstract: Abstract. The Saharan Air Layer (SAL) in the summertime eastern Atlantic is typically well mixed and 3–4 km deep, overlying the marine boundary layer (MBL). In this paper, we show experimental evidence that at times a very different structure can be observed. During the AERosol properties – Dust (AER-D) airborne campaign in August 2015, the typical structure described above was observed most of the time, and was associated with a moderate dust content yielding an aerosol optical depth (AOD) of 0.3–0.4 at 355 n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 61 publications
0
37
0
Order By: Relevance
“…As a result of these developments, observational campaigns have now shown that coarse and giant dust particles are far more prevalent, and transported further and higher than previously thought. Fennec, the Saharan Mineral Dust Experiment 1 20 (SAMUM1), Saharan Mineral Dust Experiment 2 (SAMUM2), Saharan Aerosol Long-range Transport and Aerosol-Cloud-Interaction Experiment (SALTRACE), AERosol Properties -Dust (AER-D) and Aerosol Direct Radiative Impact on the regional climate in the MEDiterranean region (ADRIMED) have all reported a significant presence of coarse to giant dust particles, despite the sampling locations of Saharan dust ranging from very close to sources to thousands of kilometres away Weinzierl et al, 2011;Ryder et al, 2013b;Ryder et al, 2018;Denjean et al, 25 2016;Marenco et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of these developments, observational campaigns have now shown that coarse and giant dust particles are far more prevalent, and transported further and higher than previously thought. Fennec, the Saharan Mineral Dust Experiment 1 20 (SAMUM1), Saharan Mineral Dust Experiment 2 (SAMUM2), Saharan Aerosol Long-range Transport and Aerosol-Cloud-Interaction Experiment (SALTRACE), AERosol Properties -Dust (AER-D) and Aerosol Direct Radiative Impact on the regional climate in the MEDiterranean region (ADRIMED) have all reported a significant presence of coarse to giant dust particles, despite the sampling locations of Saharan dust ranging from very close to sources to thousands of kilometres away Weinzierl et al, 2011;Ryder et al, 2013b;Ryder et al, 2018;Denjean et al, 25 2016;Marenco et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Flights B923 and B924 both took place on the 12 th August flying between Praia and Fuerteventura to sample the outflow from a dust uplift event that had happened on the 10 th August in Northern Mali. These flights were able to reach the main dust plume, which means that highest AOD's and extinction coefficients of the campaign were measured on this day (Marenco et al, 2018). The 335 two flights sampled the same plume at different times during the day, and only B923 is shown here as results for flight B924 are similar.…”
mentioning
confidence: 89%
“…AERosol properties -Dust (AER-D) was a collaborative campaign led by the Met Office in collaboration with the Universities of Reading and Hertfordshire (Marenco et al, 2018). It was held at the same time as the Ice in Clouds Experiment -Dust (ICE-D), a larger collaborative campaign involving the Met Office, the, National https://doi.org/10.5194/acp-2020-57 Preprint.…”
Section: Ice-d Campaignmentioning
confidence: 99%
See 1 more Smart Citation
“…(c) Effective diameter with respect to altitude, the embedded cloud layer at 4 km is evident due to the steep increase in effective diameter. The blue trace shows raw data, whilst the orange trace shows smoothed data using a 10 point moving average.3.1.2 Upsonde systemThe UCASS was used during the AERosol properties -Dust (AER-D) & Sunphotometer Airborne Validation EXperiment -Dust (SAVEX-D) campaigns over Cape Verde during August 2015(Marenco et al, 2018). A UCASS was launched as part of a balloon-based system in tandem with a GRAW DFM-09 during a Saharan dust event on the 25 th August, from Instituto Nacional De Meteorologia E Geofisica (INMG), Espargos, Sal island.…”
mentioning
confidence: 99%